Protective effect of chaige anti-alcoholic granules on acute alcoholic liver injury in rats and acute toxicity in mice - Chen, Ying; Zhao, Feiyu; Sang, Xing; Zhang, Rongzhen; Bi, Mengfei; Tang, Meimei; Wang, RongBin; Wang, Hongting; Wang, Cunqin (Frontiers in Pharmacology, 2025)
Background and aimAlcoholic liver disease (ALD), caused by consumption of alcohol, with high morbidity and mortality, whose effective interventions is essential. Chinese medicine has a long history of detoxification, and Chaige anti-alcoholic granules (CAG) is an accepted formula including 13 Chinese herbs with definite detoxifying and liver-protecting effects in clinical for acute alcohol intoxication. However, the underlying mechanism is unclear.MethodsIn this study, mice were selected for acute toxicity experiments with the increasing drug concentration to 0.78 mg⋅mL-1. Body weight changes, organ indices, liver and kidney histological observations were performed after 2 weeks. ALT, AST, BUN, and creatinine in mice serum were detected by the kits. A rat model of alcoholic liver injury (ALI) was established by gavage of Chinese wine with 56% alcohol, which was intragastrically received with CAG at 1575, 3150 and 6300 mg⋅kg⋅day-1 for 2 weeks, respectively, while positive group 100 mg⋅kg⋅day-1 metadoxine. The organ indices were measured, and the protective effect of CAG on ALI was determined using kits, ELISA, histopathology, and western blotting.ResultsThe results of the acute toxicity experiment showed that the mice were alive normally and the organ index, liver and kidney histopathology, and serum biochemical indicators showed no significant difference between the control group and the CAG-treated groups. The results of hepatoprotective effect of CAG in rat showed that compared with the control group, the liver index, ALT, AST, ADH, TC, TG, GSH-Px, SOD, and CYP450 2E1 levels were all increased in the model group (P < 0.01), while ALDH and MDA were decreased (P < 0.01). Compared with the model group, the detection indicators in the different dose CAG treatment groups could be reversed, and there was a certain dose-effect relationship, that is, the reversal effect of the high and med-dose groups was better (P < 0.01). Liver histological observation showed that CAG could alleviate the infiltration of inflammatory cells.ConclusionThese indicated that CAG had no acute toxicity and exhibited a large safety range, and was first identified to protect against hepatotoxicity through anti-oxidative stress and anti-inflammation, providing a scientific basis for further research into its clinical applications.